The Duration of Leasing Waqf Property under Frame Work of Maqasid Syariah - Awang, Abdul Bari; Abdul Razak, Wan Nazihah; Awang Abd. Rahman @ Jusoh, Amilah (2019)
The purpose of this study is to discuss the issue of duration of leasing waqf properties in the light of Maqasid Al Shariah and its provisions, as leasing is one of the important ways to invest the waqf properties. Leasing of waqf property is generally similar with the leasing of other properties, with additional provisions mainly to protect the properties and the public interest. This study focus on meaning of what is meant by Maqasid Al-Shariah first, then discuss the issue of duration for leasing waqf properties in the view of the Islamic scholars. The method employed is an analytical approach of relevant sources related to the topic, which the researchers collect sources related to the maqasid alshariah at first, then about the duration of leasing waqf properties according to the various Islamic scholars, and the researchers used this method to analyze scholars‘ view regarding this issue. The study confirmed that leasing of waqf property is generally similar with the leasing of other properties, except for the additional provisions to protect the properties and the public interest as stated in the maqasid al-shariah, and one the provisions added is the duration of leasing waqf properties